Mercy ebook - Picoult, Jodi (2011)
From #1 New York Times bestselling author Jodi Picoult comes a “sensitive exploration of the balance of love” ( Publishers Weekly ). What would you do for someone you love? Would you lie? Would you leave? Would you kill? Cameron MacDonald has spent his life guided by duty. As the police chief of a small Massachusetts town that has been home to generations of his Scottish clan, he is bound to the town's residents by blood and honor. Yet when his cousin Jamie arrives at the police station with the body of his wife and horrifying confession that he's killed her, Cam immediately places him under arrest. In the midst of betrayals and trials, forced to confront the limits of their love and loyalties, these cousins must ask themselves how far the borders of their hearts can extend.